Readiness of European laboratories for the revised EU Ambient Air Quality Directive: An interlaboratory comparison on levoglucosan, mannosan and galactosan in PM2.5 - Falk Mothes; Laurent Poulain; Jean-Luc Jaffrezo; Sophie Darfeuil; Rhabira Elazzouzi; Karl Espen Yttri; Hans Gundersen; Nicolas Bonnaire; Jean-Eudes Petit; Benjamin Bergmans; Eric Moïs; Theodoros Potouridis; et al. (Atmospheric Environment, 2026)

Comparative assessment of 24 pigment dusts reveals analogue inhalation effects - Anne Herrmann; Laura Puente; Lan Ma-Hock; Heidi Stratmann (Regulatory Toxicology and Pharmacology, 2026)

Temporal Changes to Migratory Fuel Load in Migratory Birds Across Europe - Jennifer Anne Border; Robert A. Robinson; James W. Pearce‐Higgins; Chris M. Hewson; Christine Howard; Philip A. Stephens; Stephen G. Willis; Jan A. C. von Rönn; Pierre‐Yves Henry; Romain Lorrilliere; Lorenzo Serra; Simona Imperio; et al. (Global Change Biology, 2025)
Climate change is a major threat to biodiversity, and migratory animals are particularly vulnerable, due partly to their reliance upon good resource availability across a network of sites at specific times. Migrants perform vital ecosystem functions, transferring significant resources across large spatial scales, but the impacts of climate change on the ability of individuals to complete these journeys are poorly studied. Collecting the large‐scale and long‐term data on the condition of individuals during migration to address this is challenging, but in migratory birds, we have a model system for which a large network of ringers (banders) collect individual data on body size and mass, enabling variation in body condition to be tracked. We used long‐term ringing data on 33 Afro–Palearctic migratory bird species at 286 sites across Europe to demonstrate a large‐scale decrease in migratory fuel loads during autumn over the last 40 years, but not in spring. Declines were strongest across southern Europe and linked to rising temperatures. The timing of autumn fuelling has also shifted, occurring earlier at northern sites and later at southern sites. These relationships varied depending on diet and breeding cycle length. Obligate insectivores were more constrained by temperature in the timing and magnitude of fuelling than frugivores. Species with short breeding cycles departed later at southern sites in warmer years, likely reflecting an extended breeding season. Altogether, these latitudinally varying findings suggest a trade‐off between maximising productivity or maximising adult survival as climate drives changing constraints on breeding season length and resource availability. Similar climate‐induced trade‐offs may be happening in other migratory taxa with the potential to influence population trends.

Interlinking environmental and food composition databases: An approach, potential and limitations - Cédric Furrer; Daniel Sieh; Anne-Marie Jank; Grégoire Le Bras; Moritz Herrmann; Alba Reguant-Closa; Thomas Nemecek (Journal of Cleaner Production, 2024)

Cefepime versus carbapenems for treatment of AmpC beta-lactamase-producing Enterobacterales bloodstream infections - Julia Herrmann; Anne-Valérie Burgener-Gasser; Daniel Goldenberger; Jan Roth; Maja Weisser; Pranita D. Tamma; Sarah Tschudin-Sutter (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Cefepime is recommended for treating infections caused by AmpC beta-lactamase-producing Enterobacterales (AmpC-PE), though supporting evidence is limited. Therefore, this study compared outcomes associated with cefepime versus carbapenem therapy for bloodstream infections (BSIs) caused by AmpC-PE after phenotypic exclusion of ESBL-co-producing isolates. Methods This retrospective cohort study compared definite cefepime versus carbapenem treatment for AmpC-PE BSI in hospitalized patients of the University Hospital Basel, Switzerland, between 01/2015 and 07/2020. Primary outcomes included in-hospital death, renal impairment and neurologic adverse events; secondary outcomes included length of hospital stay and recurrent infection. Results Two hundred and seventy episodes of AmpC-PE BSI were included, 162, 77 and 31 were treated with a carbapenem, cefepime and other antibiotics, respectively. Patients treated with carbapenems were more likely to be transferred to the ICU on admission and more frequently had central venous catheter as a source of infection. In uni- and multivariable analyses, primary and secondary outcomes did not differ between the two treatment groups, except for more frequent occurrence of neurological adverse events among patients treated with carbapenems and shorter length of hospital stay among survivors treated with cefepime. Conclusion After excluding isolates with phenotypic ESBL-co-production, cefepime was not associated with adverse outcomes compared to carbapenems when used to treat BSIs caused by AmpC-PE. Our study provides evidence to support the use of cefepime as a safe treatment strategy for AmpC-PE BSI, particularly in clinically stable patients without initial renal impairment or increased susceptibility to neurological adverse events.

Motorische Basiskompetenzen - Anne Strotmeyer; Miriam Kehne; Christian Herrmann (German Journal of Exercise and Sport Research, 2020)

Genome‐inferred spatio‐temporal resolution of an uncultivated Roizmanbacterium reveals its ecological preferences in groundwater - Patricia Geesink; Carl‐Eric Wegner; Alexander J. Probst; Martina Herrmann; Hang T. Dam; Anne‐Kristin Kaster; Kirsten Küsel (Environmental Microbiology, 2020)
Summary Subsurface ecosystems like groundwater harbour diverse microbial communities, including small‐sized, putatively symbiotic organisms of the Candidate Phyla Radiation, yet little is known about their ecological preferences and potential microbial partners. Here, we investigated a member of the superphylum Microgenomates ( Cand . Roizmanbacterium ADI133) from oligotrophic groundwater using mini‐metagenomics and monitored its spatio‐temporal distribution using 16S rRNA gene analyses. A Roizmanbacteria‐specific quantitative PCR assay allowed us to track its abundance over the course of 1 year within eight groundwater wells along a 5.4 km hillslope transect, where Roizmanbacteria reached maximum relative abundances of 2.3%. In‐depth genomic analyses suggested that Cand . Roizmanbacterium ADI133 is a lactic acid fermenter, potentially able to utilize a range of complex carbon substrates, including cellulose. We hypothesize that it attaches to host cells using a trimeric autotransporter adhesin and inhibits their cell wall biosynthesis using a toxin–antitoxin system. Network analyses based on correlating Cand . Roizmanbacterium ADI133 abundances with amplicon sequencing‐derived microbial community profiles suggested one potential host organism, classified as a member of the class Thermodesulfovibrionia (Nitrospirae). By providing lactate as an electron donor Cand . Roizmanbacterium ADI133 potentially mediates the transfer of carbon to other microorganisms and thereby is an important connector in the microbial community.

Vectorial transport of the plant alkaloid berberine by double-transfected cells expressing the human organic cation transporter 1 (OCT1, SLC22A1) and the efflux pump MDR1 P-glycoprotein (ABCB1) - Anne T. Nies; Elke Herrmann; Manuela Brom; Dietrich Keppler (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Increase of the Hydrophilicity of Polyethylene Terephthalate Fibres by Hydrolases from Thermomonospora fusca and Fusarium solani f. sp. pisi - Mandy Alisch-Mark; Anne Herrmann; Wolfgang Zimmermann (Biotechnology Letters, 2006)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)